PERBANDINGAN EFEKTIVITAS MEDIA KONVENSIONAL DAN DIGITAL MARKETING TERHADAP MINAT PENGUNJUNG BALI BLUES FESTIVAL NUSA DUA BALI - I Nengah Wirata (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
The use of digital marketing for tourism development must be supported by the implementation of various event activities that can attract visitors to come to enjoy various cultural attractions. Visitors who are satisfied with the events that are presented will have an impact on influencing others. The purpose of this study is to compare the effectiveness of conventional media and digital marketing on the interest of visitors to the Bali Blues Festival Nusa Dua Bali. This research was conducted with a quantitative approach by taking a sample of 100 people and using a non-probability sampling method with a purposive sampling technique. The data analysis tool used was simple linear regression analysis using the SPSS program. Version 23.0. The results show that digital marketing media has a higher level of effectiveness than conventional media with a difference in the percentage of contribution in attracting visitors to the Bali Blues Festival Nusa Dua Bali by 14%.